Pengaruh Kerja Shift terhadap Kadar Glutamic Acid Decarboxylase 65 (GAD65) dalam Serum Darah - Imam Cahyo Murwidi (Jurnal Kesehatan, 2018)
This study was to know shift work influences to increases levels of Glutamic Acid Decarboxylase 65 (GAD65) in the blood serum which is a marker of pancreatic beta cell destruction.The study method was quasi-experimental with the non-randomize pretest-posttest control group design. Subjects in this study were nurses at the R.A. Kartini Jepara hospital, female, aged 25 to 50 years, BMI 18.5 to 24.9, a work period of more than three years, did not have a routine or schedule a job outside the main working and randomize blood glucose less than 200 mg/dl. The sample size was 20 shift worker nurses and 20 non-shift worker nurses. GAD65 examination with ELISA method. The data study was analyzed with Wilcoxon test, paired t-test and independent t-test.The study results showed significant difference (p Wilcoxon test = 0.04) between the mean levels of GAD65 shift workers group pretest (0.189 ± 0.180 ng/ml) with posttest (0.334 ± 0.334 ng/ml). Not significant (p Paired t-test = 0.081) difference between the mean levels of GAD65 non-shift worker group pretest (0.326 ± 0.284 ng/ml) with posttest (0.218 ± 0.164 ng/ml). Significant (p Independent t-test = 0.008) difference between the mean delta GAD65 shift workers group (0.307 ± 0.145 ng/ml) with the non-shift workers group (- 0.107 ± 0.261 ng/ml).It can be concluded that shift work can increase GAD65 levels in blood serum but still within the normal range.